2012
DOI: 10.1371/journal.pone.0045074
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Neuronal Cell Cultures More Accurately Model Voltage Gated Calcium Channel Functionality in Freshly Dissected Nerve Tissue

Abstract: It has been demonstrated that neuronal cells cultured on traditional flat surfaces may exhibit exaggerated voltage gated calcium channel (VGCC) functionality. To gain a better understanding of this phenomenon, primary neuronal cells harvested from mice superior cervical ganglion (SCG) were cultured on two dimensional (2D) flat surfaces and in three dimensional (3D) synthetic poly-L-lactic acid (PLLA) and polystyrene (PS) polymer scaffolds. These 2D- and 3D-cultured cells were compared to cells in freshly disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 67 publications
(94 reference statements)
1
41
0
1
Order By: Relevance
“…Neural network formation and neuronal activity have also been studied in three dimensional (3D) neuronal cultures (Edelman and Keefer, 2005; Baker and Chen, 2012), in which neurons are embedded in a 3D scaffold, which enables higher and more complex connectivity (Lai et al, 2012; Ulloa Severino et al, 2016). 3D cultures relevant for activity probing include networks embedded in a extracellular matrix (ECM)-like hydrogel scaffold (Irons et al, 2008; Iwashita et al, 2014) and 3D neuronal cultures devoid of ECM (Bosi et al, 2015), which can be probed using 3D electrode arrays (Musick et al, 2009) or optical (Pautot et al, 2008) approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural network formation and neuronal activity have also been studied in three dimensional (3D) neuronal cultures (Edelman and Keefer, 2005; Baker and Chen, 2012), in which neurons are embedded in a 3D scaffold, which enables higher and more complex connectivity (Lai et al, 2012; Ulloa Severino et al, 2016). 3D cultures relevant for activity probing include networks embedded in a extracellular matrix (ECM)-like hydrogel scaffold (Irons et al, 2008; Iwashita et al, 2014) and 3D neuronal cultures devoid of ECM (Bosi et al, 2015), which can be probed using 3D electrode arrays (Musick et al, 2009) or optical (Pautot et al, 2008) approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Optical imaging methods, particularly calcium imaging (Cossart et al, 2005; Shein et al, 2008; Herzog et al, 2011; Dana et al, 2014), support neuronal population activity recording at cellular resolution, and avoid the spike sorting problem associated with extracellular electrodes. The optical alternative can also be used to show correlations between neuron activity and morphology (Cossart et al, 2005) and is particularly well suited for distributed 3D populations (Edelman and Keefer, 2005; Irons et al, 2008; Baker and Chen, 2012; Lai et al, 2012; Dana et al, 2014; Bosi et al, 2015; Ulloa Severino et al, 2016). Nevertheless, to the best of our knowledge, no study has thus far characterized the development of spontaneous activity patterns of a large neuronal population in 3D tissue-like cultures embedded in an ECM-like hydrogel scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse intuito, vários biomateriais foram testados ao longo dos anos, entre eles, o poli ácido lático (PLLA), poli caprolactona (PCL), chitosana e poliuretano [9,16,31,33] . O estudo dos biomateriais ora supracitados, entre outros, foram pesquisados não somente in vivo [14,16,34] , mas in vitro, com os diversos tipos celulares, tais como os fibroblastos, as células de Schwann e neurônios [2,11,13,16,35] . Ainda, alguns dos estudos realizados com o neuroblastoma em cultura celular foram feitos com carbono, poli ácido lático-co-glicólico (PLGA) e nanomateriais [1,12,14,32,34,36] .…”
Section: Resultsunclassified
“…Lai et al compared neuronal voltage-gated calcium channel functionality in 2D to 3D setting. [52] Primary neuronal cells were harvested from mice and either cultured onto 2D flat surfaces or in 3D synthetic polymer scaffolds, the latter consisting of PLLA and polystyrene. It was found that cells in 3D scaffolds resembled native intact tissue more closely in terms of cell morphology and ion channel functioning.…”
Section: Biomaterial-aided Three-dimensional Cell Culture Platformsmentioning
confidence: 99%